Porphyromonas gingivalis in saliva associates with chronic and aggressive periodontitis. Issue 1 (1st January 2019) - Damgaard, Christian; Danielsen, Anne Katrine; Enevold, Christian; Massarenti, Laura; Nielsen, Claus Henrik; Holmstrup, Palle; Belstrøm, Daniel
ABSTRACT: Objective : To characterize the salivary microbiota of patients with aggressive periodontitis, patients with chronica periodontitis and orally healthy individuals. Methods : A total of 81 unstimulated saliva samples from aggressive periodontitis patients (n = 31), chronic periodontitis patients (n = 25), and orally healthy controls (n = 25) were examined. The V1-V3 region of the 16S rDNA gene was sequenced with Illumina® MiSeq TM, and sequences were annotated to the expanded Human Oral Microbiome Database (eHOMD). Results : A mean percentage of 97.6 (range: 89.8–99.7) of sequences could be identified at species level. Seven bacterial species, including Porphyromonas gingivalis, were identified with significantly higher relative abundance in saliva from aggressive periodontitis patients than in saliva from orally healthy controls. Salivary abundance of P. gingivalis could discriminate aggressive (AUC: 0.80, p = 0.0001) and chronic periodontitis (AUC: 0.72, p = 0.006) from healthy controls. Likewise, salivary presence of P. gingivalis was significantly associated with aggressive (p < 0.0001, RR: 8.1 (95% CI 2.1–31.2)) and chronic periodontitis (p = 0.002, RR: 6.5 (95% CI: 1.6–25.9)). Conclusion : Salivary presence and relative abundance of P. gingivalis associate with aggressive and chronic periodontitis, but do not discriminate between aggressive and chronic periodontitis.